Transcontinental dispersal, ecological opportunity and origins of an adaptive radiation in the Neotropical catfish genus Hypostomus (Siluriformes: Loricariidae). Issue 7 (17th March 2016) - Silva, Gabriel S. C.; Roxo, Fábio F.; Lujan, Nathan K.; Tagliacollo, Victor A.; Zawadzki, Claudio H.; Oliveira, Claudio
Abstract: Ecological opportunity is often proposed as a driver of accelerated diversification, but evidence has been largely derived from either contemporary island radiations or the fossil record. Here, we investigate the potential influence of ecological opportunity on a transcontinental radiation of South American freshwater fishes. We generate a species‐dense, time‐calibrated molecular phylogeny for the suckermouth armored catfish subfamily Hypostominae, with a focus on the species‐rich and geographically widespread genus Hypostomus . We use the resulting chronogram to estimate ancestral geographical ranges, infer historical rates of cladogenesis and diversification in habitat and body size and shape, and test the hypothesis that invasions of previously unoccupied river drainages accelerated evolution and contributed to adaptive radiation. Both the subfamily Hypostominae and the included genus Hypostomus originated in the Amazon/Orinoco ecoregion. Hypostomus subsequently dispersed throughout tropical South America east of the Andes Mountains. Consequent to invasion of the peripheral, low‐diversity Paraná River basin in southeastern Brazil approximately 12.5 Mya, Paraná lineages of Hypostomus, experienced increased rates of cladogenesis and ecological and morphological diversification. Contemporary lineages of Paraná Hypostomus are less species rich but more phenotypically diverse than their congeners elsewhere. Accelerated speciation and morphological diversification rates within Paraná basin Hypostomus are consistent with adaptive radiation. The geographical remoteness of the Paraná River basin, its recent history of marine incursion, and its continuing exclusion of many species that are widespread in other tropical South American rivers suggest that ecological opportunity played an important role in facilitating the observed accelerations in diversification.